Effort To Win The Competition In Digital Business Payment Modeling - Williams, Alexander; Widayanti, Riya; Maryanti, Tatik; Julianingsih, Dwi (Pandawan Sejahtera Indonesia, 2022)
Competition in the digital payment business on an international and local scale will be increasingly intense. In the face of competitive conditions like this, digital payment companies are required to continuously develop their sources of competitive advantage through the establishment of digital business strategies and the development of digital business models that can ensure the creation of superior value for consumers and ultimately provide value to company owners. In the digital payment business, this effort requires companies not only to be able to do business but also how companies can develop knowledge and digital capabilities.